The determination of optimal cells disintegration method of Candida albicans and Candida tropicalis fungals - M. V. Rybalkyn (Zaporozhye State Medical University, 2014)
Candidiasis is common infectious disease that affects the mucous membranes, skin, nails, hair, and internal organs. Now Ukraine has neither domestic nor registered imported vaccine against candidiasis. The development of vaccine for prevention and treatment of candidiasis is a key issue in modern medicine and pharmacy. Similar research is actively conducted in many countries of the world: Russia, USA, Japan and others. It should be noted that researchers have not yet reached a consensus view which vaccine is most effective with candidiasis. There are several types of vaccines: live, inactivated, subunit and others. In this article, we consider getting the potential subunit vaccine from Candida albicans and Candida tropicalis fungi. Subunit vaccine is composed of fragments of antigens that can provide an adequate immune response. These vaccines can be represented by particles of microbes. It is known that the main substances in cells of genus Candida fungi, which have antigenic properties, are proteins and polysaccharides. However, the question of their localization in the layers of the cell wall and cytoplasm nowadays require more detailed studies. Many researchers to highlight cytoplasm antigens and all the other layers of the cell use the following methods: grinding cells with quartz sand, destroying them in different machine disintegrating, freezing and thawing a multi others. To obtain potential subunit vaccine fungi were rejected by methods that are based on the processing of biomass fungi chemicals (extraction, hydrolysis). The aim of this work was to study experimentally the destruction method of Candida albicans and Candida tropicalis fungi. Cells of Candida albicans fungi strain CCM 335-867 and Candida tropicalis fungi strain 20336 ATTS have been separately cultured in vitro on agar Sabouraud at 25 ± 2º C for 48 hours and then washed by 10 ml of sterile 0.9% isotonic sodium chloride solution. Cell suspension of Candida albicans and Candida tropicalis fungi has been prepared separately on Sabouraud agar. Incubation has been done at 25 ± 2º C for 6 days and then washed by 25 ml of sterile 0.9% isotonic sodium chloride solution. We determined the microbiological purity of cell suspension of Candida albicans and Candida tropicalis fungi visually and by microscopy. Further washings has been obtained by centrifuged at speed 3000 r / min for 10 min. The resulting precipitate of fungi has been proved by sterile isotonic 0.9% sodium chloride solution to (8,5 - 9)х108 in 1 ml of standardized suspension and by counting the cells in the Goryaeva fungi cell. For cell disruption fungi has been resorted to the action of ultrasound, rubbing with abrasive material and freeze-thaw. Key parameters in the ultrasonic disintegration are: frequency 22 kHz, the intensity of 5 W/cm2, a temperature of 25 ± 2° C, time 15 minutes, 10 ml of 0,9% isotonic sterile sodium chloride solution. For grinding fungal cells using mortar, pestle, quartz sand and biomaterial in a 1:1 ratio, and 10 mL of sterile isotonic 0,9% sodium chloride solution. Freezing and thawing have been performed in 10 ml sterile isotonic 0.9% sodium chloride solution at a temperature of -25 ± 2 ° C and 25 ± 2 ° C. In each case the amount of protein and polysaccharides has been calculated. For a more detailed analysis the monosaccharide composition has been determined in each case. It is possible to establish the optimal method of cell disruption of Candida albicans and Candida tropicalis fungi, namely ultrasonic disintegration. In the future we plan to study the immunological properties of the proteins and polysaccharides on animals.